Penerapan Model Pembelajaran Scramble terhadap Hasil Belajar IPAS Siswa Kelas V SD Negeri 85 Lubuklinggau - Syara Aprilia; Ahmad Gawdy Prananosa; Yetty Trisnayanti (Mataram University, 2026)
Student learning outcomes in Natural and Social Sciences (IPAS) at the elementary school level remain suboptimal because the instructional process is dominated by lecture methods, resulting in low student engagement. One alternative to address this issue is the implementation of the